Category classification of deformable object using hybrid dynamic model for robotic grasping - Hou Y.C.; Sahari K.S.M.; How D.N.T.; Weng L.Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
Agricultural robots; Clothes; Convolutional neural networks; Deep neural networks; Deformation; Dynamic models; Object recognition; Simulation platform; Category Classification; Deformable object; Home service robot; Hybrid dynamic modeling; Off-line simulations; Robotic manipulation; Unfolding procedures; Visual identification; Robotics